Application of water treatment technology with help solar and antimicrobial power to village communities Tanjung Selamat Sub-district Sunggal Districts Deli Serdang - Isnaini Nurwahyuni; Sinaga, Riyanto; Rizky Yudha Pratama; Fathurrahman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The need for clean water is a challenge in rural areas, especially villages that have not yet been reached by the Regional Water Company (Perusahaan Daerah Air Minum,PDAM). One of the villages experiencing problems with the availability of clean water is Tanjung Selamat Housing Village, Deli Serdang Regency. The people in this village rely solely on ground water that comes from private bore wells. The problem faced is that the water is relatively high in turbidity, and the level of water sterilization is also very low because it contains micro-organisms that cause disease such as dysentery, typhoid diarrhea and so on. An efforts to clean water using citrate have been made but the level of turbidity of the water is still above the threshold. To overcome this problem, appropriate technology is needed for water treatment to produce clean water. The purpose of this activity is to design and implement a technology to process raw water into clean water for public consumption. A design of antimicrobial water purification set with the help of solar power has been provided in Tanjung Selamat Deli Serdang Housing in 2019. The steps taken are surveying the existence of water standards, microbial laboratory testing and acidity test. Low quality raw water has obtained in the target villagewhere the water is high turbidity level, yellowish color, acidity level 6, 23 and contains coliform E.coli bacteria, so it requires processing before it is used as raw material for domestic purposes and drinking water. The application of purifying technology with the help of solar panels is able to convert raw water into clear water, has an acidity of 8.6 and is free of E. coli bacteria. The water produced is also alkaline so it is good for domestic consumption. Water user communities really feel the benefits of appropriate water purification technology developed in community service activities